2020
DOI: 10.1101/2020.12.11.20247551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling of aerosol transmission of airborne pathogens in ICU rooms of COVID-19 patients with acute respiratory failure

Abstract: The COVID-19 pandemic has generated many concerns about cross-contamination risks, particularly in hospital settings and Intensive Care Units (ICU). Virus-laden aerosols produced by infected patients can propagate throughout ventilated rooms and put medical personnel entering them at risk. Experimental results found with a schlieren optical method have shown that the air flows generated by a cough and normal breathing were modified by the oxygenation technique used, especially when using High Flow Nasal Canula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
0
10
0
3
Order By: Relevance
“…The numerical model based on CFD techniques proposed in the current study was defined to evaluate face coverings on airborne transmission risks and, therefore, no empirical or statistical model was included for modeling the rate of infection. Crawford et al [38] showed that the assessment of the exposure time and/or the minimum viral load required to become infected is relevant. The risk of infection could be found by using a dose-response equation, along with the total amount of virus present in the air and the exposure time; see the case study evaluating the risk of infection by Adhikari et al [39].…”
Section: Discussionmentioning
confidence: 99%
“…The numerical model based on CFD techniques proposed in the current study was defined to evaluate face coverings on airborne transmission risks and, therefore, no empirical or statistical model was included for modeling the rate of infection. Crawford et al [38] showed that the assessment of the exposure time and/or the minimum viral load required to become infected is relevant. The risk of infection could be found by using a dose-response equation, along with the total amount of virus present in the air and the exposure time; see the case study evaluating the risk of infection by Adhikari et al [39].…”
Section: Discussionmentioning
confidence: 99%
“…A N U S C R I P T 3 sneeze, and talking produced from the oral cavity (Johnson et al, 2011;Lee et al, 2019;Stadnytskyi et al, 2021;El Hassan et al, 2022), as well as aerosol dispersion inside a room (Inthavong et al, 2013;Heschl et al, 2014;Ji et al, 2018;Tao et al, 2020;Bathula et al, 2021;Crawford et al, 2021;Shah et al, 2021;Shrestha et al, 2021) and outdoor environments (Feng et al, 2020;Gorbunov, 2021). Additionally, studies (Zhu et al, 2006;Scharfman et al, 2016) demonstrated the oral cough produced a droplet-laden cough jet and puff dynamics, as well as review articles on the fluid dynamics of respiratory droplets (Dbouk and Drikakis, 2020;Mittal et al, 2020;Katre et al, 2021), and mitigation strategies for reducing viral transmission (Hui et al, 2012;Khosronejad et al, 2020;Salati et al, 2021).…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…La pandémie COVID-19 a suscité de nombreuses inquiétudes quant aux risques de contamination croisée en milieu hospitalier. Les aérosols chargés de virus produits par les patients infectés peuvent se propager dans les pièces mal ventilées et mettre en danger les soignants et les patients non infectés [1] .…”
Section: Introductionunclassified
“…
Introduction La pandémie COVID-19 a suscité de nombreuses inquiétudes quant aux risques de contamination croisée en milieu hospitalier. Les aérosols chargés de virus produits par les patients infectés peuvent se propager dans les pièces mal ventilées et mettre en danger les soignants et les patients non infectés [1] .
Objectif Caractérisation du mode de transmission air de SARS Cov-2, lors de deux clusters Covid-19 en janvier et avril 2021 dans un service de Pneumologie.
…”
unclassified